Role of Endothelial Nitric Oxide Synthase in Diabetic Nephropathy: Lessons from Diabetic eNOS Knockout Mice - Takamune Takahashi; Raymond C. Harris (Journal of Diabetes Research)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease in many countries. The animal models that recapitulate human DN undoubtedly facilitate our understanding of this disease and promote the development of new diagnostic markers and therapeutic interventions. Based on the clinical evidence showing the association of eNOS dysfunction with advanced DN, we and others have created diabetic mice that lack eNOS expression and shown that eNOS-deficient diabetic mice exhibit advanced nephropathic changes with distinct features of progressive DN, including pronounced albuminuria, nodular glomerulosclerosis, mesangiolysis, and arteriolar hyalinosis. These studies clearly defined a critical role of eNOS in DN and developed a robust animal model of this disease, which enables us to study the pathogenic mechanisms of progressive DN. Further, recent studies with this animal model have explored the novel mechanisms by which eNOS deficiency causes advanced DN and provided many new insights into the pathogenesis of DN. Therefore, here we summarize the findings obtained with this animal model and discuss the roles of eNOS in DN, unresolved issues, and future investigations of this animal model study.